The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1469-8986.2010.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of language switching in second language learners

Abstract: This study analyzed the electrophysiological correlates of language switching in second language learners. Participants were native Spanish speakers classified in two groups according to English proficiency (high and low). Event-related potentials (ERPs) were recorded while they read English sentences, half of which contained an adjective in Spanish in the middle of the sentence. The ERP results show the time-course of language switch processing for both groups: an initial detection of the switch driven by lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
88
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 52 publications
(75 reference statements)
18
88
8
Order By: Relevance
“…Thus, the language nodes of the prime words are presumed to inhibit the target language lexical representations in switch trials and/or to enhance the activation of the same-language lexical representations in non-switch trials (see also Duñabeitia et al, 2010b). Other ERP studies have shown similar patterns (Martin et al, 2012;Midgley et al, 2009a;Proverbio et al, 2004;Van Der Meij et al, 2011), but to date no ERP study has investigated the contribution of orthographic cues. However, the time-course of visual word recognition based on results from experiments using masked priming relies on the interpretation of the N250 as typically associated with the mapping of orthographic units onto orthographic word forms (see Grainger & Holcomb, 2009, for a review), and the N400 with a later stage of processing sensitive to interactions between lexical forms and semantic representations.…”
Section: Introductionmentioning
confidence: 67%
“…Thus, the language nodes of the prime words are presumed to inhibit the target language lexical representations in switch trials and/or to enhance the activation of the same-language lexical representations in non-switch trials (see also Duñabeitia et al, 2010b). Other ERP studies have shown similar patterns (Martin et al, 2012;Midgley et al, 2009a;Proverbio et al, 2004;Van Der Meij et al, 2011), but to date no ERP study has investigated the contribution of orthographic cues. However, the time-course of visual word recognition based on results from experiments using masked priming relies on the interpretation of the N250 as typically associated with the mapping of orthographic units onto orthographic word forms (see Grainger & Holcomb, 2009, for a review), and the N400 with a later stage of processing sensitive to interactions between lexical forms and semantic representations.…”
Section: Introductionmentioning
confidence: 67%
“…eye movement recordings)language background questionnaire and self-ratings of proficiencyLiu, Guo, and Peng, (2009)neural organization of L1 and L2 productionL1 and L2 picture namingself-ratings of proficiencyMacizo, Bajo, and Cruz Martin, (2010)processing of interlingual homographsword relation judgmentslanguage background questionnaire and self-ratings of proficiencyMidgley, Holcomb, and Grainger, (2009)time-course of form and meaning activation during L2 word recognitionvisual word identification (animal name detection)language background questionnaire and self-ratings, L2-L1 translation of experimental itemsOta, Hartsuiker, and Haywood, (2009)L2 recognition of near-homophonessemantic relationship judgmentlanguage background questionnairePalmer, van Hooff, and Haavelka, (2010) (Exp. 1)word–concept mapping in bilingual memorytranslation recognition and ERPslanguage background questionnaire and self-ratings of proficiencyvan der Meij, Cuetos, Carreiras, and Barber, (2011)language switching, role of proficiencysentence reading (incl. ERPs) in-house English aptitude test (60 multiple-choice questions on grammar and vocabulary) Verhoef, Roelofs, and Chwilla, (2010)language switchingpicture naming with language switching (incl.…”
Section: Introductionmentioning
confidence: 99%
“…The few ERP studies that have analyzed code switching in a sentence context have observed a code switching effect on the left anterior negativity (LAN) or N400 amplitude, where switched words elicited larger negative amplitude than non-switched words (Moreno, Federmeier, & Kutas, 2002; Proverbio, Leoni, & Zani, 2004; van Der Meij, Cuetos, Carreiras, & Barber, 2011). …”
Section: Introductionmentioning
confidence: 99%